2017
DOI: 10.5901/mjss.2017.v8n3p69
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of User Intention in Using e-Learning Technology in Indonesian Context: An Empirical Study

Abstract: At present, through the help of the internet, an increasing number of higher education institutions worldwide encourages faculty and students to adopt e-Learning in spite of the many barriers still exists in its implementation. This study presents how organizational factors and ease of use influence perceived usefulness and intention to use e-Learning. For this purpose, three hundred and ninety four samples collected from students of seven higher institutions in Southeast Sulawesi of Indonesia were surveyed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For example, organizational support for innovation (OSI), namely 'the expectation, approval, and practical support of attempts to introduce new and improved ways of doing things in the work environment' [69] (p. 28), seems to be a key factor that can facilitate the adoption of new technologies [38]. Indeed, some studies found significant relationships among OSI and the usefulness/ease of use of technology [69][70][71][72], as well as intention to use [73]. On the contrary, a lack of organizational support can undermine the company's efforts to introduce new technology [38,74].…”
Section: Organizational Variablesmentioning
confidence: 99%
“…For example, organizational support for innovation (OSI), namely 'the expectation, approval, and practical support of attempts to introduce new and improved ways of doing things in the work environment' [69] (p. 28), seems to be a key factor that can facilitate the adoption of new technologies [38]. Indeed, some studies found significant relationships among OSI and the usefulness/ease of use of technology [69][70][71][72], as well as intention to use [73]. On the contrary, a lack of organizational support can undermine the company's efforts to introduce new technology [38,74].…”
Section: Organizational Variablesmentioning
confidence: 99%
“…With the Internet getting more powerful day by day and along with it are the e-learning environments as one of the direct beneficiaries, researchers and academicians have been extending their studies into advanced courses and fields such as Engineering [5], Mathematics [6], Economics [7], Physics [8], Medicine [9] and many more just to dive deeper into students' perceptions. Apart from these, there are also a lot of research papers that extensively studied factors that affect e-learning technology readiness and acceptance in different setting from neighboring countries such as Malaysia [10][11], Thailand [12][13], Indonesia [14][15] to a not so much outside Asia like Turkey [16] and Sri Lanka [17] up to other continents like Africa [18] and America [19].…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with past studies like Davis (1989), Venkatesh and Davis (1996), Muk and Chung (2015), Sanchez-Prieto et al (2016) who also found that perceived ease of use positively affects customers' intention of using SST. According to Tanduklangi (2017) and Setiawan et al (2018), the level of individual intention on using SST increases when the person feels it is relatively simple to operate the technology without over-relying on others for help.…”
Section: Resultsmentioning
confidence: 99%